Impact of macro-scale circulation types on the occurrence of frosty days in Poland - Tomczyk, Arkadiusz Marek (Bulletin of Geography. Physical Geography Series, 2015)
The research aimed at determining variability of occurrence of frosty days in Poland and defining the impact of macro-scale circulation types on these days occurrence from December to March. The study used daily data concerning the minimum, maximum and mean daily air temperature for 15 stations located in Poland from 40 winter seasons between 1970/71 and 2009/10. In the predominantly large area of Poland; in the analysed multiannual period, a decrease in the number of frosty days was noticed; still, these changes were not statistically significant. The conducted research study showed that the North Atlantic Oscillation and the Scandinavian type had the most significant impact on the number of frosty days in Poland.